2012
DOI: 10.3389/fnmol.2012.00056
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the calcium-binding protein calretinin, not of calbindin D-28k, causes a permanent impairment of murine adult hippocampal neurogenesis

Abstract: Calretinin (CR) and calbindin D-28k (CB) are cytosolic EF-hand Ca2+-binding proteins and function as Ca2+ buffers affecting the spatiotemporal aspects of Ca2+ transients and possibly also as Ca2+ sensors modulating signaling cascades. In the adult hippocampal circuitry, CR and CB are expressed in specific principal neurons and subsets of interneurons. In addition, CR is transiently expressed within the neurogenic dentate gyrus (DG) niche. CR and CB expression during adult neurogenesis mark critical transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
(124 reference statements)
2
21
0
Order By: Relevance
“…The role of CR in immature neurons has been proposed, and CR knockout mice show reduced survival and migration of newborn neurons in the DG (Todkar et al . ). Therefore, it is hypothesized that elevated CR expression in immature neurons may selectively contribute to the survival effect of ECS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The role of CR in immature neurons has been proposed, and CR knockout mice show reduced survival and migration of newborn neurons in the DG (Todkar et al . ). Therefore, it is hypothesized that elevated CR expression in immature neurons may selectively contribute to the survival effect of ECS.…”
Section: Discussionmentioning
confidence: 97%
“…The increase in CR(+) cells in the DG has also been reported for other stimuli that increase neurogenesis, such as enriched environments, running, and kainate‐induced seizures (Todkar et al . ). It should be noted that Brandt et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous work showed that chronic treatment with melatonin increased the number of CR-neurons in the DG of young C57Bl6 mice (Ramirez-Rodriguez et al, 2009). Calretinin is a Ca ++ -binding protein (Kuznicki et al, 1996;Schwaller, 2014) that is essential for neuronal development in the DG during adulthood (Brandt et al, 2003;Todkar et al, 2012). In this sense, it has been proposed that in maturing granule cells, CR could function as a Ca ++ -sensor during Ca ++ transients occurring with the onset of synaptic activity and also linked to the GABA-dependent depolarizing currents (Ge et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This protein acts as a calcium-buffer/binding (Schwaller, 2014) and is essential for murine hippocampal neurogenesis (Brandt et al, 2003;Todkar et al, 2012). During aging CR-protein expression and the number of CR-neurons decrease in the whole hippocampus (Bu et al, 2003;Lee et al, 2010;Mirochnic et al, 2009).…”
Section: Introductionmentioning
confidence: 98%